The Impact of Parent–Teacher Communication on Student Behaviour and Social Development in a Semi-Government School in Fujairah - ALMARSHOODI, ALYAZYAH (2024)
In the realm of contemporary education, proficient communication between parents and instructors assumes a crucial role in moulding student conduct and fostering social growth. This study investigates the influence of parent–teacher communication on student results at a semi-government school located in Fujairah, the United Arab Emirates. A total of ten parents were included in this research study, which utilised a mixed-methods approach that included both questionnaires and interviews. The study analyses the main difficulties and advantages that exist in the communication between parents and teachers in the specific educational environment. The participants shared their experiences, perceptions, and expectations about communication strategies through questionnaires and interviews. The data analysis reveals several aspects that impact the efficiency of communication, such as cultural norms, technology capabilities, and institutional backing. Evidence indicates that although the significance of communication between parents and teachers is acknowledged, many obstacles impede its effective execution. The obstacles encompass language difficulties, restricted technology infrastructure, and cultural disparities in communication preferences. Nevertheless, the participants also emphasised the advantages of robust parent–teacher contact, including enhanced student engagement, behaviour, and overall academic achievement. In addition, the study examines methods to improve parent–teacher communication, including the use of multilingual communication platforms, regular feedback systems, and culturally sensitive approaches. The Interviews provided valuable insights into the intricate factors that contribute to the development of meaningful partnerships between parents and instructors. This research has important implications for educational stakeholders, policymakers, and practitioners who want to improve student outcomes by encouraging effective collaboration between parents and teachers. By tackling the identified issues and capitalising on the chances for enhancement, schools can establish a suitable atmosphere for comprehensive student development. Ultimately, this study adds to the expanding collection of research on parent–teacher communication and its influence on student behaviour and social development. It emphasises the significance of cultivating cooperative partnerships between parents and teachers to bolster the educational progress of pupils in semi-government schools in Fujairah and other areas.